Selectivity Analysis for Simulated Natural Gas Mixtures Separation via Adsorption on Zeolite 13 X as Solid Desiccants - BALABID, AHMED MOHAMMED OBAID (IRC, 2016)
The increased demand for more cost effective and eco-friendlier techniques in natural gas separation and purification opens the opportunity for more studies related to CO2 removal from raw natural gas, before gas sent to the onshore processing. In this study a gravimetric technique used to study selectivity of CO2/CH4 adsorption on 13X Zeolites at 50 and 70oC and pressure up to 10 bars. 13X showed high CO2 adsorption capacity. While at the same time low adsorption capacity for CH4, which considered as un-adsorptive component. In this project both, pure component mixtures of CO2 and CH4 and binary mixture of both of them have been analyzed. For pure component mixture, six isotherm models utilized to analyze the experimental adsorption data. And 13X Zeolite showed high agreement with Langmuir model where the adsorbed follows a monolayer adsorption behavior (the layer of the adsorbed substance is one molecule in thickness)